Case study: GPR survey at the archaeological Roman site of Ciavieja, El Ejido (Spain). Issue 5 (1st February 2013) - Faize, Ahmed; de Jong van Coevorden, C.M.; Cobos Sánchez, C.; Fernández Pantoja, A.; Gonzalez García, S.; Driouach, Abdellah; Gómez Martín, R.
ABSTRACT: This paper, describing a ground‐penetrating radar (GPR) survey performed on the archaeological site of Ciavieja, El Ejido (Spain), is part of a series of historical studies performed in Ciavieja to analyse the extent and importance of the remains buried at this site. The objective of the GPR survey was to locate the most promising areas within the archaeological site to help design a park that combines leisure and culture. The time slices built with the radar data show several locations with linear and square anomalies with sizes compatible with those of Roman walls or rooms. The interpretation of the GPR data is corroborated with FDTD computer simulations.